Velocity Control of Visco-Elastic Materials Movement in the Cylindrical Channel of the Grinder Feed Screw of the Former - Fomenko E.; Nugmanov A. (Техника и технология пищевых производств)
The present research features the problems of wheat processing. Wheat processing has its own specific features. For instance, the process of gluten extrusion forming is very complex since it is associated with the visco-elastic and adhesive properties of raw gluten. The article discusses the results of applying the numerical finite difference method to the Navier-Stokes equation in the case of the one-dimensional problem when a cooled viscoelastic material has to pass through circular nozzles. The paper also features the obtained surface model of velocity evolution and some averaged results for the possible automation of the process. The viscosity properties of raw gluten are variable and depend on temperature, chemical composition, and properties of the raw material. Modeling makes it possible to characterize the properties of the material and its behavior in various situations. Such research demands neither additional time nor significant costs. The authors identified patterns of movement for raw gluten in the extrusion molding unit and selected the most appropriate automation system to control the speed of its movement to the molding assembly in the grinder feed screw. The significance of the research is obvious for subsequent physical and mathematical modeling of heat and mass transfer processes of vacuum freezing and drying and granulating of gluten extrusions. The results of the research presented in the article are consistent with the available information on this topic. The present approach to solving the problem of choosing the best rational hydrodynamic regimes was applied due to the complexity of the experimental determination of velocity fields and the difficulty of analyzing the Navier-Stokes system of hydrodynamic differential equations with variable proportionality coefficients.